2004
DOI: 10.1177/147323000403200313
|View full text |Cite
|
Sign up to set email alerts
|

Change in Serum Concentrations of Interleukin-2 and Interferon-γ during Treatment of Tuberculosis

Abstract: We aimed to investigate changes in serum concentrations of the cytokines interleukin (IL)-2 and interferon (IFN)-gamma during the clinical course of active tuberculosis, to establish the presence of cellular immunity before and after treatment. Blood samples were taken from 18 patients with active tuberculosis before and 2 months after therapy; IL-2 and IFN-gamma concentrations were evaluated. The mean serum IL-2 concentration before therapy was 164.5 pg/ml (range 12-980 pg/ml) and the concentration 2 months a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…(14,15) Our results show that patients with PTB also present increased pretreatment CRP levels, when compared production during treatment was also demonstrated in another study. (25) Although variable, IFN-γ levels in the patients with PTB were lower after two months of treatment than at the onset of the treatment. (25) Finally, a number of authors have observed that PBMCs submitted to various antigenic stimuli present high production of IFN-γ before and after treatment in patients with tuberculosis.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…(14,15) Our results show that patients with PTB also present increased pretreatment CRP levels, when compared production during treatment was also demonstrated in another study. (25) Although variable, IFN-γ levels in the patients with PTB were lower after two months of treatment than at the onset of the treatment. (25) Finally, a number of authors have observed that PBMCs submitted to various antigenic stimuli present high production of IFN-γ before and after treatment in patients with tuberculosis.…”
Section: Discussionmentioning
confidence: 92%
“…(25) Although variable, IFN-γ levels in the patients with PTB were lower after two months of treatment than at the onset of the treatment. (25) Finally, a number of authors have observed that PBMCs submitted to various antigenic stimuli present high production of IFN-γ before and after treatment in patients with tuberculosis. (20)(21)(22) Another cytokine that participates in the formation of granulomas is TNF-α, levels of which are high in the pleural fluid, plasma or monocyte culture of patients with tuberculosis, before or after the onset of the treatment, when compared with chronic patients or individuals without tuberc.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is known that IFN-c was shown to induce autophagic control of tuberculosis infection [25], thus influencing the waining of specific response with time after infection [26], and high levels of IFN-c have been found in the bloodstream [15,27] and lungs [16,17] of TB patients with active disease. Also, TNF-a is involved in the initial and long-term progression of TB and in macrophage activation along with recruitment of cells to the infected area [5].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of serum IL-2 and IFN-γ levels in 18 active tuberculosis patients at the initial phase and during the 2nd month of therapy showed an apparent decrease of these two cytokines after treatment. Since there was no control group, these authors could not state whether the cytokine levels had regressed to values in healthy individuals (Berktas et al 2004). In our study, IL-2 levels were also significantly reduced by the 2nd month of treatment but had returned to healthy control values by the 4th month.…”
Section: Röllinghoff 2001) It Is Well Known That Cd4+mentioning
confidence: 99%